THE FACTORS INFLUENCING ECONOMIC GROWTH IN INDONESIA - Dian Citra Amelia; Sri Fajar Ayu (Universitas Negeri Medan, 2019)
This research is based on the fact that the state of economic growth in Indonesia tends to fluctuate, even more often decrease. This is because the government policy is not appropriate to improve the economic growth of Indonesia. This study aims to determine and analyze the factors of foreign direct investment, inflation, international trade, and government expenditure that affect economic growth in Indonesia. The problem in this research is due to the limited fund in economic development both structure and infrastructure so that economic growth tends to decrease. Therefore, appropriate strategies must be taken to overcome the limitations in promoting economic growth. From this problem, this research aims to see how big influence of foreign direct investment (FDI), inflation (INF), international trade (NX) and government expenditure (GE) variable to economic growth. The data used in this study is secondary data (periodical data) in the period of observation 1996-2014 obtained from the World Bank and Statistics of Indonesia. To identify the influence of the variables used in this study used the VAR (Vector Autoregression) method. The results of this study show that equation regression shows that FDI (-1) has a negative influence on economic growth and FDI (-2) has a positive effect on economic growth, INF (-1) and INF (-2) have positive effects on economic growth , Variable NX (-1) has a positive effect on economic growth but NX (-2) has a negative effect on economic growth, and GE variable (-1) has a positive effect on economic growth while GE (-2) has a negative effect on growth Economy.